Dissipation of Earthward Propagating Flux Rope Through Re‐reconnection with Geomagnetic Field: An MMS Case Study. Issue 9 (9th September 2019) - Poh, Gangkai; Slavin, James A.; Lu, San; Le, Guan; Ozturk, Dogacan Su; Sun, Wei‐Jie; Zou, Shasha; Eastwood, Jonathan P.; Nakamura, Rumi; Baumjohann, Wolfgang; Russell, Christopher T.; Gershman, Daniel J.; et al.
Abstract: Three‐dimensional global hybrid simulations and observations have shown that earthward‐moving flux ropes (FRs) can undergo magnetic reconnection (or re‐reconnection) with the near‐Earth dipole field to create dipolarization front (DF)‐like signatures that are immediately preceded by brief intervals of negative B Z . The simultaneous erosion of the southward B Z field at the leading edge of the FR and continuous reconnection of lobe magnetic flux at the X‐line tailward of the FR result in the asymmetric south‐north B Z signature in many earthward‐moving FRs and possibly DFs with negative B Z dips prior to their observation. In this study, we analyzed Magnetospheric MultiScale (MMS) observation of fields and plasma signatures associated with the encounter of an ion diffusion region ahead of an earthward‐moving FR on 3 August 2017. The signatures of this re‐reconnection event were (i) +/− B Z reversal, (ii) −/+ bipolar‐type quadrupolar Hall magnetic fields, (iii) northward super‐Alfvénic electron outflow jet of ~1, 000–1, 500 km/s, (iv) Hall electric field of ~15 mV/m, (v) intense currents of ~40–100 nA/m 2, and (vi) J·E′ ~0.11 nW/m 3 . Our analysis suggests that the MMS spacecraft encounters the ion and electron diffusion regions but misses the X‐line. Our results are in good agreement with particle‐in‐cell simulations of Lu et al. (2016, https://doi.org/10.1002/2016JA022815 ). We computed a dimensionless reconnection rate of ~0.09 for this re‐reconnection event and through modeling, estimating that the FR would fully dissipate by −16.58 R E . We demonstrated pertubations in the high‐latitude ionospheric currents at the same time of the dissipation of earthward‐moving FRs using ground‐ and space‐based measurements. Key Points: Observations of the fields and plasma signatures associated with the encounter of a re‐reconnection X‐line and its ion diffusion region Our observations indicate that the leading edge of earthward flux rope is being eroded through re‐reconnection with the geomagnetic field Ground‐ and space‐based measurements show correlation between the dissipation process of earthward flux ropes and auroral substorm activity